2008
DOI: 10.1110/ps.073134408
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of a disulfide bond to the structure, stability, and dimerization of human IgG1 antibody CH3 domain

Abstract: Recombinant human monoclonal antibodies have become important protein-based therapeutics for the treatment of various diseases. The antibody structure is complex, consisting of b-sheet rich domains stabilized by multiple disulfide bridges. The dimerization of the C H 3 domain in the constant region of the heavy chain plays a pivotal role in the assembly of an antibody. This domain contains a single buried, highly conserved disulfide bond. This disulfide bond was not required for dimerization, since a recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 44 publications
6
67
0
Order By: Relevance
“…[43][44][45] We have opined that engineering of the heterodimer such that it retains its thermal stability should function as an indirect indicator that the engineered design is equivalent to the wild type Fc in the interchain pairing and stabilization. In addition, proper folding and stability of the CH3 domain could also contribute to the monomer-dimer equilibrium, 45 thus a stable CH3 heterodimer improves the homogeneity of the engineered antibody.…”
Section: Figure 1 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] We have opined that engineering of the heterodimer such that it retains its thermal stability should function as an indirect indicator that the engineered design is equivalent to the wild type Fc in the interchain pairing and stabilization. In addition, proper folding and stability of the CH3 domain could also contribute to the monomer-dimer equilibrium, 45 thus a stable CH3 heterodimer improves the homogeneity of the engineered antibody.…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…[43][44][45] We have opined that engineering of the heterodimer such that it retains its thermal stability should function as an indirect indicator that the engineered design is equivalent to the wild type Fc in the interchain pairing and stabilization. In addition, proper folding and stability of the CH3 domain could also contribute to the monomer-dimer equilibrium, 45 thus a stable CH3 heterodimer improves the homogeneity of the engineered antibody. From an application perspective, the next generation of antibody designs could very well involve bispecific antibodies that are themselves antibody drug conjugates, 46 and given that drug conjugation reactions tend to affect the stability and observed Tm of the parent antibody, 47 a more stable heterodimeric Fc can improve the manufacturability of these classes of therapeutics.…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…34,35 Recently, however, the impact that a reduced disulfide bond can play in multidomain antibodies has recently come to light. 27 Lacy et al demonstrated a correlation between antibody thermal stability and the extent of free cysteines present in a series of antibodies, with greater free cysteines translating to lower thermal stability.…”
Section: Implications For Monoclonal Antibody Aggregationmentioning
confidence: 99%
“…[13][14][15][16][17][18] The reason for disulfide stabilization has been attributed to both entropic and enthalpic effects. One theory suggests that a decrease in entropy of the unfolded state is causing destabilisation of this state compared with the folded state.…”
Section: Introductionmentioning
confidence: 99%